2018
DOI: 10.1180/mgm.2018.107
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of mansfieldite (AlAsO4·2H2O), angelellite (Fe4(AsO4)2O3) and kamarizaite (Fe3(AsO4)2(OH)3·3H2O)

Abstract: Thermodynamic data for the arsenates of various metals are necessary to calculate their solubilities and to evaluate their potential as arsenic storage media. If some of the less common arsenate minerals have been shown to be less soluble than the currently used options for arsenic disposal (especially scorodite and arsenical iron oxides), they should be further investigated as promising storage media. Furthermore, the health risk associated with arsenic minerals is a function of their solubility and bioavaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…21 The hydrated aluminum arsenate is part of the variscite mineral group, and one end of the solid solution series between mansfieldite and scorodite, the iron analog. That scorodite and mansfieldite are a solid solution series also means iron and aluminum (as Fe 3+ and Al 3+ ) more easily swap for each other in the mineral structure; in mineral systems this substitution often has a thermodynamic limit, as yet undefined here, 22 but significant Fe substitution is possible in a particular mansfieldite mineral grain. The iron detected alongside arsenic in the white pigment studied here as evidenced by SEM-EDS and MA-XRF mapping suggests that the pigment found in the thangkas is not high enough in iron to significantly alter the structure of the atoms from mansfieldite, as specific techniques like Raman spectroscopy and XRD are sensitive to these changes and the results here are consistent with the white material being primarily mansfieldite.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…21 The hydrated aluminum arsenate is part of the variscite mineral group, and one end of the solid solution series between mansfieldite and scorodite, the iron analog. That scorodite and mansfieldite are a solid solution series also means iron and aluminum (as Fe 3+ and Al 3+ ) more easily swap for each other in the mineral structure; in mineral systems this substitution often has a thermodynamic limit, as yet undefined here, 22 but significant Fe substitution is possible in a particular mansfieldite mineral grain. The iron detected alongside arsenic in the white pigment studied here as evidenced by SEM-EDS and MA-XRF mapping suggests that the pigment found in the thangkas is not high enough in iron to significantly alter the structure of the atoms from mansfieldite, as specific techniques like Raman spectroscopy and XRD are sensitive to these changes and the results here are consistent with the white material being primarily mansfieldite.…”
Section: Resultsmentioning
confidence: 97%
“…The relative solubility of mansfieldite is decreased in a solution with even minor amounts of Al 3+ based on calculations using available thermodynamic data. 22 Although sources of mansfieldite in Tibet have not to the authors’ knowledge been specifically reported in the literature, it is conceivable that the mineral was procured locally from primary hydrothermal ore deposits or from the abundant deposits of weathered arsenic sulfides, likely associated with at least some aluminum-bearing minerals. According to the early 1900s Richmond, Virginia newspaper reports concerning the Stone collection of Himalayan paintings, 3,4 the artworks were procured in Chamdo in Tibet.…”
Section: Resultsmentioning
confidence: 99%